Compound weather and climate extremes in the Asian region: science-informed recommendations for policy - Krishnan, R.; Dhara, Chirag; Horinouchi, Takeshi; Gotangco Gonzales, C. Kendra; Dimri, A. P.; Shrestha, M. Singh; Swapna, P.; Roxy, M. K.; Son, Seok-Woo; Ayantika, D. C.; Cruz, Faye Abigail T.; Qiao, Fangli (Frontiers in Climate, 2025)
Anthropogenic climate change has led to rapid and widespread changes in the atmosphere, land, ocean, cryosphere, and biosphere, leading to more pronounced weather and climate extremes globally. Recent IPCC reports have highlighted that the probability of compound extreme events, which can amplify risk, has risen in multiple regions. However, significant gaps remain in our understanding of the drivers and mechanisms behind these events. This concept paper discusses compound events in the Asian region in the context of its unique and diverse geographical settings, and regional climatic features including the seasonal monsoons. Notably, Asia is the world’s most disaster-affected region due to weather, climate, and water-related hazards. Therefore, an integrated understanding of how climate change will impact compound events in this region is essential for effective forewarning and risk mitigation. This paper analyzes three typologies of compound events in the Asian region, illustrating their regional complexity and potential linkages to climate change. The first typology pertains to compound floods, for example, the devastating floods in the Indus River Basin and adjoining Western Himalayas during 2022 caused by the combined effects of heavy monsoon rainfall, intense pre-monsoon heatwaves, glacier melt, and modes of climate variability. The second typology relates to compound heatwave-drought events that have prominently manifested in East and South Asia, and are linked to large-scale drivers of the land-atmosphere–ocean coupled system and local feedbacks. The third typology relates to marine extremes involving the compounding effects of ocean warming, sea-level rise, marine heatwaves, and intensifying tropical cyclones. We identify key knowledge gaps in understanding and predicting compound events over the Asian region and discuss advances required in science and technology to address these gaps. We also provide recommendations for the effective utilization of climate information towards improving early warning systems and disaster risk reduction.